Catatonia in autism spectrum disorder: Analysis of clinical characteristics, stressful life events, and validation of the attenuated behavior questionnaire (ABQ) - Esen Öksüzoğlu, Makbule; Rollas, Tahsin; Erdoğan, İ. Mert; Aliyev, E. Selin Akbaş; Ünal, Dilek; Karahan, Sevilay; Esen, Tuna Çak; Yağcıoğlu, A. Elif Anıl (Psychiatry research, 2025)
Autism spectrum disorder (ASD) and catatonia exhibit overlapping motor and behavioral symptoms; however, catatonia is often underdiagnosed in individuals with ASD. This study evaluates the validity and reliability of the Turkish version of the Attenuated Behavior Questionnaire (ABQ) and explores the clinical characteristics of individuals with ASD and catatonia. The study involved 300 participants with ASD, aged 12-25 years. Parents completed the ABQ, Repetitive Behavior Scale (RBS), and Aberrant Behavior Checklist (ABC), while clinicians evaluated catatonia using DSM-5 criteria, the Bush Francis Catatonia Rating Scale (BFCRS), KANNER Scale, and Childhood Autism Rating Scale (CARS). Regression in social and language skills and stressful life events from the previous six months were also assessed. The mean age of participants was 16.0 years, with 32 (10.7 %) diagnosed with catatonia; among these, 15.3 % experienced regression, and 25.0 % reported stressful life events. The ABQ showed strong validity and reliability (Spearman-Brown coefficient = 0.979), with ROC analysis determining diagnostic (92.5) and screening (39.5) cut-off points. Participants with ASD and catatonia had significantly elevated rates of late regression, impairments in social and language skills, psychiatric comorbidities, and stressful life events, and they scored considerably higher on BFCRS, KANNER, CARS, RBS, and ABC (all p < .05). Our findings highlight high prevalence of catatonia among individuals with ASD and its association with late regression, social and language impairments, psychiatric comorbidities, and stressful life events and underscore the clinical utility of the ABQ in identifying catatonic symptoms in ASD and emphasize the importance of early recognition and intervention.